A study of heat treatment of high‐boron high‐speed steel roll. Issue 7 (16th July 2013) - Cen, Q.; Fu, H.
Abstract High‐boron high‐speed steel (HSS) is a cheap roll material. In the paper, the authors research the effect of heat treatment on the microstructure and properties of high‐boron high‐speed steel HSS roll containing 0.54% C, 1.96% B, 3.82% W, 7.06% Mo, 5.23% Cr and 2.62% Al by means of the optical microscopy (OM), the scanning electron microscopy (SEM), X‐ray diffraction (XRD) and hardness test. The results showed that as‐cast structure of boron‐bearing high‐speed steel HSS consisted of martensite, pearlite, M2(B, C), M3(B, C) and M23(B, C)6 type borocarbides. After quenching, the matrix transformed into the lath martensite, and M3(B, C) dissolved into the matrix. When quenching temperature is lower than 1050°C, the hardness is increased with the increase of quenching temperature under oil cooling, while quenching temperature excels 1100°C, the hardness will decrease with the increase of quenching temperature. Under the condition of salt bath and air cooling, the effect of quenching temperature on the hardness is similar to the above law, but the quenching temperature obtaining the highest hardness is higher than that of oil cooling. The highest hardness is obtained while tempering at 525°C. The hardness of high‐boron high‐speed steel HSS roll is 66.5 HRC, and its impact toughness excels 13.1 J/cm2. Using in pre‐finishing stands of high‐speed hot wire‐rod rolling mill, the wear rate of high‐boron HSS rolls is 0.26 mm/one thousand tons steel. However the manufacturing cost of high‐boron HSS rolls is obviously lower than that of powder metallurgy hard alloy rolls, it is only 28% of that of powder metallurgy (PM) hard alloy rolls.